2021
DOI: 10.1371/journal.pntd.0009467
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiological investigation and physician awareness regarding the diagnosis and management of Q fever in South Korea, 2011 to 2017

Abstract: Background In South Korea, the number of Q fever cases has rapidly increased since 2015. Therefore, this study aimed to characterize the epidemiological and clinical features of Q fever in South Korea between 2011 and 2017. Methods/Principal findings We analyzed the epidemiological investigations and reviewed the medical records from all hospitals that had reported at least one case of Q fever from 2011 to 2017. We also conducted an online survey to investigate physicians’ awareness regarding how to appropri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…We inferred that the patient was likely infected by inhaling C. burnetii aerosols at the slaughterhouse. Q fever is still a severely neglected infectious disease in the global animal disease detection system, and Q fever's daily monitoring and diagnosis are insufficient (20)(21)(22)(23). Therefore, the effective prevention of zoonotic diseases is significant to public health safety (24).…”
Section: Discussionmentioning
confidence: 99%
“…We inferred that the patient was likely infected by inhaling C. burnetii aerosols at the slaughterhouse. Q fever is still a severely neglected infectious disease in the global animal disease detection system, and Q fever's daily monitoring and diagnosis are insufficient (20)(21)(22)(23). Therefore, the effective prevention of zoonotic diseases is significant to public health safety (24).…”
Section: Discussionmentioning
confidence: 99%
“…Currently, no studies have been published regarding detection of C. burnetii in environmental samples from South Korea. The large differences in the incidence of human Q fever in many regions of South Korea (from 0.01 cases per 100,000 persons per year in Incheon city to 0.53 cases per 100,000 persons per year in Chungbuk province) (Kim et al., 2021) suggest that the distribution of infected animal reservoirs may vary substantially nationwide. During a large Q fever outbreak in the Netherlands, control measures focusing on areas around Q fever‐infected dairy farms led to the successful control of the outbreak (Roest et al., 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Epidemiologic studies of human Q fever in South Korea show that 14–23% of confirmed patients have high‐risk occupations (agricultural farmers, livestock raisers, veterinarians and slaughterhouse workers); however, the majority of patients (77–86%) do not have high‐risk occupations or contact with animals (Kim et al., 2021; Heo et al., 2019). These findings suggest that many reservoirs of C. burnetii are undetected in South Korea.…”
Section: Introductionmentioning
confidence: 99%
“…In an epidemiological study of Q fever in South Korea, the average incidence rate was as low as 0.07 cases per 100,000 persons per year all across the country from 2011 to 2017, which increased sharply to 0.19 cases per 100,000 persons in 2017. 16 Especially, Midwestern areas such as Chungbuk (0.53 cases per 100,000 persons per year) and Chungnam (0.27 cases per 100,000 persons per year) showed a much higher incidence than other areas. One of the epidemiological characteristics of patients with Q fever is that 24% of all reported cases were related to occupational contact with animals or animal products.…”
Section: Changing Epidemiology Of Human and Animal Q Fever In Koreamentioning
confidence: 94%